1989
DOI: 10.1111/j.1540-8159.1989.tb06151.x
|View full text |Cite
|
Sign up to set email alerts
|

Actuarial Incidence and Pattern of Occurrence of Shocks Following Implantation of the Automatic Implantable Cardioverter Defibrillator

Abstract: The actuarial incidence and pattern of occurrence of shocks were analyzed in 65 patients after implantation of the automatic implantable cardioverter defibrillator. During a mean follow-up of 25 +/- 21 months only one patient died suddenly, and this patient had a nonfunctioning device at the time of death. The long-term actuarial risk of death from any cause in the patients who received appropriate shocks was not significantly different than for the entire group. The 1- and 4-year cumulative risk of receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
1

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(34 citation statements)
references
References 10 publications
5
28
0
1
Order By: Relevance
“…Electrocardiographic documentation at the time of ICD shock was not available for all patients. However, the criteria for appropriate shock used in our study are in accordance with criteria used by other investigators [3, 8, 9, 14]. The fact that our data regarding shock incidence are similar to the results of other investigators [15, 16], ranging from 62 to 69% in 5 years, make it unlikely that we overestimated the incidence of appropriate shocks.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Electrocardiographic documentation at the time of ICD shock was not available for all patients. However, the criteria for appropriate shock used in our study are in accordance with criteria used by other investigators [3, 8, 9, 14]. The fact that our data regarding shock incidence are similar to the results of other investigators [15, 16], ranging from 62 to 69% in 5 years, make it unlikely that we overestimated the incidence of appropriate shocks.…”
Section: Discussionsupporting
confidence: 76%
“…All patients were seen routinely every 1–3 months or after each device discharge. An appropriate shock by the cardioverter-defibrillator was defined as a discharge preceded by symptoms of severe light-headness, presyncope, syncope followed by immediate relief from these symptoms [9], or a discharge for ventricular tachycardia or ventricular fibrillation as documented by stored cycle lengths or stored electrograms. Inappropriate device discharges were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 With "shock-only" devices, the incidence of these events during long-term follow-up has ranged between 16% and 21%. 16,17 Fromer et al 18 reported inappropriately detected episodes in 10 of 102 patients with implants during an average follow-up period of 9.4 months. In the present study, 116 of the 778 patients with implants or of the 294 patients with a therapy delivered experienced inappropriate episode detection followed by a therapy, despite a short follow-up time.…”
Section: Inappropriate Therapymentioning
confidence: 99%
“…Circumstances of shock delivery were evaluated, and number of discharges while the patient was on the waiting list was documented. Appropriate shocks were defined as previously described by Fogoros et al 19 as spontaneous ICD discharges preceded by symptoms of severe lightheadedness, presyncope or syncope, or shocks for ventricular tachycardia or ventricular fibrillation as documented by Holter monitoring or stored ECGs by the device.…”
Section: Follow-upmentioning
confidence: 99%